Antimicrobial evaluation of selected naturally occurring oxyprenylated secondary metabolites. Issue 16 (17th August 2016) - Di Giulio, Mara; Genovese, Salvatore; Fiorito, Serena; Epifano, Francesco; Nostro, Antonia; Cellini, Luigina
Abstract: This study tested the antimicrobial activity of eight selected naturally occurring oxyprenylated secondary metabolites against Staphylococcus aureus ATCC 29213, S. epidermidis ATCC 35984, Escherichia coli ATCC 8739, Pseudomonas aeruginosa ATCC 9027 and Candida albicans ATCC 10231. Results showed a moderate antimicrobial activity. The most active compounds were 3-(4-geranyloxyphenyl)-1-ethanol (4 ) and 3-(4-isopentenyloxyphenyl)-1-propanol (5 ) that were tested on mature and in-formation biofilms of all micro-organisms, moreover the cytotoxic activity was evaluated. Except for S. epidermidis, both compounds reduced significantly ( p  < 0.05) the microbial biofilm formation at 1/2 MIC and 1/4 MIC, in particular, compounds4 and5 at each concentration, inhibited E. coli biofilm formation to a greater extent, the biofilm formation was never more than 44% in respect to the control, moreover both compounds showed a low cytotoxic effect. Oxyprenylated derivatives may be of great interest for the development of novel antimicrobial therapeutic strategies and the synthesis of semi-synthetic analogues with anti-biofilm efficacy. Graphical abstract: